Design and In Silico Modeling of Heterocyclic-based Xanthone Derivatives as Potential Anticancer Agents Through Tyrosine Kinase Inhibition - Kurniawan, Yehezkiel Steven; Yudha, Ervan; Fatmasari, Nela; Yogaswara, Radite; Pranowo, Harno Dwi; Sholikhah, Eti Nurwening; Jumina, Jumina (UI Scholars Hub, 2026)
Cancer is one of the deadliest diseases nowadays, and tyrosine kinase receptors play crucial roles in cancer cell survival, differentiation, proliferation, and migration. This study designed and developed a new inhibitor from heterocyclic-based xanthone derivatives to target two tyrosine kinase receptors, epidermal growth factor receptor (EGFR) and platelet-derived growth factor receptor (PDGFR), through in silico screening. Eighteen heterocyclic-based xanthones were evaluated through molecular docking for both receptors. All heterocyclic-based xanthones gave the root mean square deviation (RMSD) value lower than 2.00 Å. Xanthone with isobenzothiazole substituent (iBzThio) was found as the most potent inhibitor with binding energies of -10.60 and -12.90 kcal/mol against EGFR and PDGFR, respectively. Further investigation has been performed through molecular dynamics (MD) simulation for 100 ns. From the results of MD simulations, i.e., RMSD, root mean square fluctuation, radius of gyration, solvent accessible surface area, hydrogen bonds, and binding energy parameters, as well as secondary structure fraction, dictionary of protein secondary structure, and Ramachandran plot, iBzThio demonstrated good stability to interact with the active site of both receptors. The binding energies of IBzThio against EGFR and PDGFR receptors were -12.58 and -12.61 kcal/mol after the MD simulations, indicating its potential application as an effective tyrosine kinase inhibitor.